GAMBARAN DISFUNGSI SEKSUAL DISABILITAS DAN KUALITAS HIDUP PADA PASIEN PASCASTROKE - Hasanul Arifin,* Alfansuri Kadri,* Yuneldi Anwar* (NEURONA, 2019)
INTRODUCTION SEXUAL FUNCTION AND DISABILITY ARE POSTSTROKE COMPLICATIONS THAT CAN AFFECT THE LONGTERM QUALITY OF LIFE THE PROBLEM IS BEING NEGLECTED THUS CANNOT BE INTERVENED FURTHER THERE ARE SIMPLE SCREENINGS THAT CAN BE USED TO DETECT THE DISORDER